Impact of histone post-translational modification inhibitors on lifespan, reproduction, and stress response in the rotifer Brachionus manjavacas - Nelia Luviano Aparicio; Meghan Dryburgh; Colleen M. McMaken; Alyssa Liguori; Kristin E. Gribble (PLoS ONE, 2025)
Epigenetic modifications, including histone post-translational modifications, are central drivers of age-associated structural and functional changes in the genome, influencing gene expression and leading to changes in cellular resilience. Epigenetic modifications are thus a target for therapies to prevent or treat age-related decline in health and lifespan. In this study, we measured the effects of inhibiting histone deacetylases (HDACs) and the histone methyltransferase, SETDB1, on lifespan, reproduction, and stress response in the rotifer Brachionus manjavacas , a model organism for aging studies. Rotifers were exposed to three pharmaceutical compounds, the HDAC inhibitors β-hydroxybutyrate and sodium butyrate and the SETDB1 inhibitor mithramycin A. Changes in global histone modification levels, lifespan, reproduction, and heat stress resistance were quantified. Global histone acetylation levels increased with β-hydroxybutyrate and sodium butyrate treatments. Histone 3 lysine 9 trimethylation (H3K9me3) levels were reduced by treatment with mithramycin A. β-hydroxybutyrate significantly extended lifespan without modifying heat stress resistance. In contrast, mithramycin A increased both lifespan and heat stress tolerance. Sodium butyrate specifically improved heat stress resistance without affecting lifespan. Importantly, none of the three treatments had a significant impact on lifetime reproduction. These findings provide insights into the role of histone modifications in aging and suggest potential interventions targeting epigenetic marks to promote longevity and resilience.